2016
DOI: 10.1155/2016/3825037
|View full text |Cite
|
Sign up to set email alerts
|

Association of Insulin Resistance with Glucose and Lipid Metabolism: Ethnic Heterogeneity in Far Western China

Abstract: Objective. To study the relationships between IR and glucose and lipid metabolism in far western China and these relationships' ethnic heterogeneity. Methods. From the baseline survey, 419 Uygur cases, 331 Kazak cases, and 220 Han cases were randomly selected, resulting in a total of 970 cases for study. FINS concentration was measured by radioimmunoassay. Results. (1) In the Kazak population, IR was correlated with hyperglycemia; high levels of TC, TG, and LDL-C; and low levels of HDL-C and abdominal obesity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 12 publications
1
17
1
Order By: Relevance
“…Insulin resistance is a major causative factor in T2DM. Defects in insulin signaling and disordered glucose and lipid metabolism account for the progression of insulin resistance [44]. Liver, adipose tissue and skeletal muscles are the major peripheral organs in regulating lipid and glucose metabolism and play important roles in controlling insulin sensitivity [45].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance is a major causative factor in T2DM. Defects in insulin signaling and disordered glucose and lipid metabolism account for the progression of insulin resistance [44]. Liver, adipose tissue and skeletal muscles are the major peripheral organs in regulating lipid and glucose metabolism and play important roles in controlling insulin sensitivity [45].…”
Section: Discussionmentioning
confidence: 99%
“…However, China is a multi-ethnic country with at least 55 ethnic groups. There are few studies focused on MetS among different ethnic groups in China, and most of these studies focused on a single ethnic group [7,12,13]. The heterogeneity in study design, inclusion criteria and definition of MetS makes it difficult to compare the prevalence in different ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 High triglyceride (TG) and low high-density lipoprotein cholesterol (HDL-C) levels are traditional risk factors for insulin resistance (IR) and T2DM. [8][9][10][11] Some studies have suggested that the TG/HDL ratio is closely related to IR, 11,12 but data on the association between the TG/HDL-C ratio and T2DM are limited, especially in Chinese people. So far, only one cohort study of 687 individuals in China explored the association, finding that the TG/HDL-C ratio independently increased the risk of T2DM in a general population.…”
Section: Introductionmentioning
confidence: 99%